Argentina’s Participation in the International Penal and Penitentiary Congress (1872-1950) - González, Esteban (2020)
This article analyzes the participation of Argentine delegates in international prison congresses held between 1872 and 1950. We argue that the forms of participation can be divided into two. On the one hand, the presence of non-penitentiary experienced representatives, generally diplomats assigned to the places where the congresses were held. On the other hand, the participation of outstanding penitentiary specialists, both for their theoretical training (in Criminal Law) and for their daily management of the Argentinian prisons. For a better development, we will divide the article in two sections. In the first one, it will be dealt with from the first congress held in London (1872) to the sixth one held in Budapest (1905). In the second part, we will analyze from the seventh congress held in Washington (1910) to the last one held in The Hague (1950). It should be noted that for the preparation of this article we have used unpublished material located in the Archive of the Argentine Foreign Office and Ministry of Justice and Education; and other published texts.